3D airway model to assess airway dead space. Issue 3 (19th September 2018) - Nieves, Ashley; Cozzo, Ashley; Kosoff, Zora; Traube, Chani; Groves, Alan M
Abstract : High flow therapy works partly by washout of airway dead space, the volume of which has not been quantified in newborns. This observational study aimed to quantify airway dead space in infants and to compare efficacy of washout between high flow devices in three-dimensional (3D) printed airway models of infants weighing 2.5–3.8 kg. Nasopharyngeal airway dead space volume was 1.5–2.0 mL/kg in newborns. A single cannula device produced lower carbon dioxide (CO2 ) levels than a dual cannula device (33.7, 31.2, 23.1, 15.9, 10.9 and 6.3 mm Hg vs 36.8, 35.5, 32.1, 26.8, 23.1 and 18.8 mm Hg at flow rates of 1, 2, 3, 4, 6 and 8 L/min, respectively; p<0.0001 at all flow rates). Airway pressure was 1 mm Hg at all flow rates with the single cannula but increased at higher flow rates with the dual cannula. Relative nasopharyngeal airway dead space volume is increased in newborns. In 3D-printed airway models, a single cannula high flow device produces improved CO2 washout with lower airway pressure.